Pesticide use and Their Impacts on Health of Farmers: A Study in Rajapur Area, Bardiya (Nepal) - Chaudhari, Bhesh Raj (Voice: A Biannual & Bilingual Journal, 2023)
A study was conducted in the Rajapur municipality and Geruwa Rural municipality to determine the types of pesticides used in agriculture and their potential effects on farmers' health. Interviews were conducted with 240 farmers from 12 villages in the study area, and the information provided suo moto by the farmers were analyzed. This study found that the farmers frequently use pesticides in the extremely risky to highly deadly categories, such as carbamates, pyrethroids, organophosphides, and organophosphates. It has been discovered that the majority of farmers in the study area are ignorant of the dangers to human health presented by the mentioned pesticides and the consequences of their careless handling. Farmers cover their faces with cloth fabric masks and smoke tobacco to protect them. In addition, it was noticed that after spraying the pesticides, other typical farming activities continued in the agricultural fields. So, there is also a possibility that these pesticides will directly come into touch with women, children, and other field employees. There were numerous illnesses and physiological abnormalities with various indications and symptoms. A significant relative risk (RR) was also noted. It was discovered that the farmers of the study area have poor state of health which was aggravated by the lack of awareness and failure to implement suitable preventive measures regarding use of pesticides.